Social media paradox: Utilizing social media technology for creating better value for better social outcomes: Case of developing countries - Binesh Sarwar; Arslan Sarwar; Waleed Mugahed Al-Rahmi; Abeer S Almogren; Said Salloum; Mohammad Habes (Cogent Business & Management, 2023)
This study presents a research framework based on the underlying richness of social media capacity (usefulness) at the individual level of youngsters regarding their contribution to building social capital and civic engagement, which significantly leads towards better social outcomes. Using structural equation modeling (SEM) technique, analysis of model accorded an examination of the impact of social media use for literacy and socialization on the perceived value in terms of social capital and civic engagement; resulting in greater cognitive and social well-being of young participants. By considering the social facets of social media technology, which can also mainly influence the value developed from the online social network, the authors also examined the moderating role of individual social technology fit in the fitting paradigms. The results support all proposed hypotheses in the model except one. This study concludes that social media tools as an interactive and productive mechanism can progressively enhance youth participation in public affairs for overall cognitive and social well-being. The positive sense of involvement is more satisfied by having an appropriate fit between individuals' social needs and social technology.
Keywords: 650; civic engagement; cognitive well-being; social capital; Social media; social well-being; social-technology fit